Queer Travels: Networked Society, Digitizing Queerness and Political Surveillance - Wong, Yuenmei (AoIR Selected Papers of Internet Research, 2013)
Queer epistemology confronts and critiques not only the regimes of heteronormativity, but also other kinds of hierarchies and normative regimes. In line with such genealogy, this paper aims to examine how queer politics as a site of global connection contrast with the lived experiences of queer people in homophobic society, especially in the era of globalization with the proliferation of information and communication technologies.